“I would have wanted to have less children”: Thoughts by migrant women regarding their sexual and reproductive rights - Hernández, Carolina Sánchez (2021)
The research tries to deepen in the analysis of different thoughts expressed by Nicaraguan migrant women in Costa Rica regarding their life experiences related to sexual education, the decision of having children, the sexual affective negotiations in couple relations, sexual violence, economic exclusion and the complex conditions to exercise their sexual and reproductive rights in the migration context. Among the main results, the living of forced motherhoods, lack of educative tools during childhood and adolescence, as the multiple forms of violence, stands out. The capacity to articulate and resistance practices, mainly with other women, to create strategies for survival, are underlined. Other aspects that stand out, besides, are the reflexive clarity regarding their life experiences and the current handling of their right to choose.